ADMINISTRATION OF SALACCA ZALACCA FRUIT ON CHANGES IN HEMOGLOBIN LEVELS IN EMESIS GRAVIDARUM IN BANJARNEGARA DISTRICT - umi fajri; Dian Nirmala Sari (Universitas Karya Husada Semarang, 2024)
The consequences of emesis gravidarum are unbalanced nutritional intake, dehydration and anemia can occur during pregnancy. A non-pharmacological alternative to reduce nausea and increase hemoglobin levels is by consuming fresh salak fruit. The aim of the research is that salak fruit can increase the hemoglobin levels of pregnant women TM I. This type of research is quasi-experimental, pretest post test control group design. The sample consisted of 30 pregnant women who experienced nausea and vomiting. The treatment in the intervention group was consumption of 100 mg salak fruit plus 30 mg vitamin B6 per day for 10 days and the control group received 30 mg vitamin B6 plus counseling about nutrition for pregnant women in the first trimester. Before the intervention was given, hemoglobin was measured and on day 11 it was measured again. .Statistical test with paired t test analysis and independent t test. The results were that there was an average change in hemoglobin levels in the intervention group, namely 0.041 mmHg, while there was no change in the control group. Research shows that 100 mg of salak fruit given for 10 days can increase Hb by 0.41 gr%.